Aktivitas Belajar Pada Penggunaan Platform Kelas Pintar dalam Pembelajaran Sejarah Pada Masa Pandemi - Ristikasari, Iis (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
The COVID-19 pandemic in Indonesia has caused the implementation of learning to be carried out online or remotely by utilizing technology as a communication liaison between teachers and students. Therefore, during this pandemic, an online learning platform is essential. Each school has its policy on choosing a learning platform for the optimal implementation of online learning. One is SMA YWKA Bandung, which uses the Kelas Pintar learning platform. The purpose of this study is to describe the learning activities of class XI MIPA 2 SMA YWKA Bandung using the Kelas Pintar platform, especially in history learning, so that this research can provide information to all related parties, especially regarding learning activities using the Kelas Pintar platform. This study uses a qualitative descriptive method to assist researchers in obtaining information and describing what is being studied in depth. Researchers managed to find several things, such as (1) Implementation of learning using the Kelas Pintar platform, which shows student learning activities in online implementation, (2) Finding learning obstacles using the Kelas Pintar platform and efforts being made to minimize learning obstacles that occur felt by teachers and students.